Characteristic study of PSAC adsorbent modified with metal oxide nanoparticles for H2S removal / Muhamad Faizul Azzim Azamuddin and Dr. Norhusna Mohamad Nor - Azamuddin, Muhamad Faizul Azzim; Mohamad Nor, Norhusna (2020)
The focus of this research is to synthesised the metal oxide nanoparticles impregnated on PSAC and to study the effects of the adsorbents on removal of H2S. The H2S gas in the presence of air is capable to cause corrosion on the metal surface. H2S is a colourless gas that also give harmful effect to the environment and human health. Therefore, it is essential to eliminate the H2S gas before it is release to the atmosphere. Metals oxide nanoparticles was synthesised via alkaline precipitation method. The metal oxide nanoparticles that was synthesised were CeO2, NiO, CuO, and Fe2O3. The metal oxide nanoparticles were undergoes SEM analysis, EDX analysis and TGA analysis. İt was found that the average size of the CeO2 is 66.5 nm, NiO is 91.46 nm, CuO is 91.26 nm, and Fe2O3 is 37.17 nm in the SEM analysis. İn the TGA analysis, it was found that the calcine temperature of these metal oxide nanoparticles for remove impurities in the metals oxide nanoparticles were CeO2 is 250 ̊C, NiO is 450 ̊C, CuO is 300 ̊C, and Fe2O3 is 600 ̊C. The synthesised metals oxide were impregnated in the pre-oxidised PSAC adsorbents (Ce/PSAC, Ni/PSAC, Cu/PSAC and Fe/PSAC). These adsorbents were undergoes FTIR analysis. İn this analysis the adsorbents shows the present of graphite groups, carbonyl group, alcohol group, carboxyl group and also free element. These adsorbents also were study the effects of different metal oxide nanoparticle impregnated on PSAC for removal of H2S. İt shows that different metals oxide nanoparticles impregnated on PSAC shows the different the breakthrough time and the adsorption capacity of the adsorbent. Based on the result of the sorption, the metals oxide nanoparticles impregnated on PSAC adsorbent is more efficient than raw PSAC adsorbent. İt shows that Cu/PSAC has the higher adsorption capacity (86.60 mg H2S/g Cu/PSAC) and breakthrough time (80 minutes) than raw PSAC which has adsorption capacity 2.85 mg H2S/g raw PSAC and the breakthrough time is 3 minutes. From overall perspective of MO/PSAC, Ce/PSAC has 4 minutes of breakthrough time and 4.03 mg H2S/g Ce/PSAC of adsorption capacity, Ni/PSAC has 9 minutes of breakthrough time and 9.06 mg H2S/g Ni/PSAC of adsorption capacity, and Fe/PSAC has 10 minutes of breakthrough time and 11.08 mg H2S/g Fe/PSAC of adsorption capacity which shows the Cu/PSAC adsorbent is the best adsorbent of MO/PSAC.